1988
DOI: 10.1007/bf01872157
|View full text |Cite
|
Sign up to set email alerts
|

Proline porters effect the utilization of proline as nutrient or osmoprotectant for bacteria

Abstract: Proline is utilized by all organisms as a protein constituent. It may also serve as a source of carbon, energy and nitrogen for growth or as an osmoprotectant. The molecular characteristics of the proline transport systems which mediate the multiple functions of proline in the Gram negative enteric bacteria, Escherichia coli and Salmonella typhimurium, are now becoming apparent. Recent research on those organisms has provided both protocols for the genetic and biochemical characterization of the enzymes mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 156 publications
(160 reference statements)
4
104
0
Order By: Relevance
“…A comparable domain was also found in ProP, the secondary transport system for glycine betaine and proline in E. coli (8). As shown for BetP, the ProP system is effectively regulated on the level of activity (14,32). It was suggested that the carboxy-terminal extension of ProP is associated with the ability to sense an osmoregulatory cellular signal (8).…”
Section: Fig 4 Glycine Betaine Uptake Of Betp Disruption Strain Betpmentioning
confidence: 53%
“…A comparable domain was also found in ProP, the secondary transport system for glycine betaine and proline in E. coli (8). As shown for BetP, the ProP system is effectively regulated on the level of activity (14,32). It was suggested that the carboxy-terminal extension of ProP is associated with the ability to sense an osmoregulatory cellular signal (8).…”
Section: Fig 4 Glycine Betaine Uptake Of Betp Disruption Strain Betpmentioning
confidence: 53%
“…Betaine is taken up by Escherichia coli and Salmonella typhimurium on transporters designated Pro P and Pro U, both identified originally as transport systems mediating uptake ofproline. Both systems have higher affinity for betaine than for proline, and the activity ofboth is increased in bacteria shifted to hypertonic media, the former increasing by > 10-fold, and the latter increasing > 100-fold (17). Transcription from the Pro U promoter has been reconstituted in vitro and shown to be stimulated by direct action of high concentrations of potassium glutamate (18), the major intracellular salt of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that the observed glutamate-H+-Na ÷ symport is the result of two activities (transport systems), i.e., GltS-mediated glutamate-Na ÷ symport [65] and GltP-mediated glutamate-H + symport [50]. A similar situation holds for proline transport in E. coli and S. typhimurium where the transport activities have been resolved to PutP-mediated proline-Na ÷ and ProPmediated proline-H ÷ symport activities [60,66,67]. The possibility that bacteria often possess more than one mechanism to transport a solute has to be taken into consideration when studies are performed under relatively undefined conditions, i.e., when purified proteins, defined host strains and/or cloned genes are not available.…”
Section: Ii-c Electrogenic Solute-cation Symport (mentioning
confidence: 95%